EMPOWERING LEADERSHIP, QUALITY OF PEOPLE DAN QUALITY OF WORK METHODS DALAM MENDORONG KESIAPAN INDIVIDU UNTUK BERUBAH - Arizqi Arizqi; Olivia Fachrunnisa (Universitas Mercu Buana, 2017)
Abstract: Individual readiness to change is an important factor and indispensable inthe process of organizational change. Aspects of 'people' and 'methods' can affect anindividual's readiness to change. This study aims to fill the research gap that has notbeen observed in the literature about individual readiness to change through the qualityof human resources and quality of working process. Besides, this study also purposes togive theoretical contribution related to the importance of empowering leadership rolethrough the people dimension (employee engagement) and work method dimention(culture of innovation) in affecting the individual‟s readiness to change. We SEM(Structural Equation Modeling) test statistical software SmartPLS to test model. Thepopulation of this study was 100 civil servants in all departments/agencies inSemarang. The results showed that Empowering Leadership influenced EmployeeEngagement, and Innovation Culture. While Employee Engagement significantlyeffects on Readiness to Change, and Innovation Culture does not significantly effect onReadiness to Change. The implication of this research is the leader of an organizationshould maximize the role of leadership that empowers or empowering leadership ininfluencing the readiness of individuals that exist within the organization to changetowards better.